A Needs-based Analysis of Information Literacy Cultivation among Contemporary University English Teachers in China - Su, Huanan; Ma, Fengyi (Universitas Ahmad Dahlan, 2024)
The current study intends to expose and analyze a needs-based analysis of information literacy cultivation in English language teaching among contemporary university English teachers in China. Twenty English teachers from a Chinese medical university participated in the current research and were asked to answer purposefully designed questionnaires. A follow-up interview was also conducted to collect further data regarding information literacy cultivation in the English language teaching practice based on a needs analysis. The current research results have shown a strong need for information literacy cultivation in English language teaching among contemporary university English teachers and a severe lack of guidance for information literacy cultivation in the English language teaching practice. The research ultimately further suggests that university teaching stakeholders, including school leaders and relevant experts, should also guide university English teachers to meet the needs of selecting proper modes of information literacy cultivation in the English language teaching sensibly and facilitate them to fully develop their teaching styles and habits as possible as they can in their English language teaching practice.